THE RELATIONSHIP OF EMESIS GRAVIDARUM WITH THE INCIDENT OF ANEMIA IN THE MOTHER PREGNANT - Permata Sari, Septi Indah; Susilawati, Elly (JURNAL IBU DAN ANAK, 2024)
Hyperemesis gravidarum is nausea and vomiting which is categorized as severe if a pregnant woman vomits every time she drinks or eats. Meanwhile, pregnancy anemia is a "potential danger to mother and child" a condition of red blood cell deficiency during pregnancy. The aim of this research is to determine the relationship between emesis gravidarumin and the incidence of anemia in the Taman Sari 6 Pratama Clinic working area. This research is an analytical survey using a cross sectional approach. This research was carried out from February to July 2022. The population in this study was all pregnant women who underwent pregnancy checks from February to August, totaling 44 TM I and II pregnant women. The sampling technique in this research was carried out using a total sampling technique that met the inclusion and exclusion criteria. The research results were analyzed using univariate and bivariate analysis with the chi-square test. Of the 44 respondents, 26 respondents (59.1%) did not experience anemia, and 18 respondents (40.9%) experienced anemia, 31 respondents (70.5%) experienced emesis, and 13 respondents ( 29.5%) did not experience emesis. There is a significant relationship between Emesis Gravidarum and Anemia in pregnant women in the Taman Sari 6 Pratama Clinic Working Area with a p value of 0.02 (p < 0.05). Based on the research results, it can be concluded that there is a relationship between hyperemesis gravidarum and anemia in pregnant